Solid lipid nanoparticle delivery of rhynchophylline enhanced the efficiency of allergic asthma treatment via the upregulation of suppressor of cytokine signaling 1 by repressing the p38 signaling pathway. Issue 1 (1st January 2021) - Lv, Chuanfeng; Li, Hui; Cui, Hongxia; Bi, Qianyu; Wang, Meng
ABSTRACT: Allergic asthma is one of the most common chronic airway diseases, and there is still a lack of effective drugs for the treatment of allergic asthma. The purpose of this work is to formulate rhynchophylline (Rhy)-solid lipid nanoparticles (SLNs) to improve their therapeutic efficacy in a mice allergic model of asthma. A solvent injection method was employed to prepare the Rhy-SLNs. Physicochemical characterization of Rhy-SLNs was measured, and the release assessment was investigated, followed by the release kinetics. Next, a model of murine experimental asthma was established. Mice were subcutaneously injected with 20 μg ovalbumin mixed with 1 mg aluminum hydroxide on days 0, 14, 28, and 42 and administrated aerosolized 1% ovalbumin (w/v) by inhalation from day 21 to day 42. Mice were intraperitoneally injected with 20 mg/kg Rhy-SLNs or Rhy at one hour before the airway challenge with ovalbumin. The results showed that Rhy-SLNs revealed a mean particle size of 62.06 ± 1.62 nm with a zeta potential value of −6.53 ± 0.04 mV and 82.6 ± 1.8% drug entrapment efficiency. The release curve of Rhy-SLNs was much higher than the drug released in phosphate buffer saline at 0, 1, 1.5, 2, 4, or 6 h. Moreover, Rhy-SLNs exerted better effects on inhibiting ovalbumin-induced airway inflammation, oxidative stress, airway remodeling (including collagen deposition and mucus gland hyperplasia) than Rhy in murine experimental asthma. Subsequently, we found that Rhy-SLNs relieved allergic asthma via the upregulation of the suppressor of cytokine signaling 1 by repressing the p38 signaling pathway.